(3GdETGQI Edi SjQI GdeUWaj hJGQjN ef HYOg ef GdNdaGAs - (3oenZrdWGj Hf nbpdjL Hf YHO Gddg GdHcLQj GdeUQj GdMcQj GdMfaj, CHh YHO Gddg, YdGA GdOjf , J (B762 (3g` s
(3ChdgG (B:s
(3HYO MeO Gddg GdbgGQ , hGdUdGI hGdSdGe Ydi GdeUWai GdeNJGQ hBdg hUMHg GdCWgGQ , WQai Gddjd hGdfgGQ EdN s
(3BNQgG (B:s
(3hEf GdCQV dG JGcd dMe GdCfHjGA Udi Gddg Ydjg hSGFQ GdfHjjf hBdg hSGFQ GdTgOGA hGdUGdMjf jdi Pdc edNU dJGQjN GdNdaGA GdQGTOjf hef HYOge Edi SbhW HZOGO Ydi jO ghdGch s
(3HBLQg ELGRIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B275 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B313s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B12 s
Keywords: (3GdJGQjNs